The Campylobacter jejuni CiaD effector co-opts the host cell protein IQGAP1 to promote cell entry - Nicholas M. Negretti (Nature Portfolio, 2021)
The pathogen Campylobacter jejuni invades intestinal cells after secreting protein effectors into the host cell cytosol via the flagellum. Here, Negretti et al. show that one of these effectors, CiaD, binds to host protein IQGAP1, thus leading to unconstrained activity of small GTPase Rac1, which modulates actin reorganization and bacterial internalization.